FEATURES OF INVESTMENT IN THE REAL ESTATE MARKET - Kobzan, S.; Pomortseva, O.; Ivakhnenko, A.; Tolstа M. (Municipal economy of cities. Series: «Economy science», 2022)
The aim of the article is to study the interaction between the rental market and the real estate market. They are considered by researchers as separate components of the real estate market in the urban development of Kharkiv. The relevance of the study is to determine the return on investment in real estate. The authors set the capitalization rate for different segments of the real estate market, namely – studya, one-bedroom, three-bedroom apartments. My research is of great importance for the prospects of modern urban economy. The question of the dependence of the rent on the cost of housing and the attractiveness of certain segments of the housing market is determined. An analysis of the cost of rent and sale for each segment and depending on the location. Factors that significantly affect the cost of sales and rent have been studied. Conclusions are made about the sustainable development of the real estate market in the city of Kharkiv and promising areas of investment. A study of the residential real estate rental market in Kharkiv was conducted. Data were collected on rental rates as of February 1, 2022 in all districts of Kharkiv. A study of the market of purchase and sale of residential real estate in Kharkov. The collection of real estate value data as of February 1, 2022 was collected in all districts of Kharkiv. Statistics on average prices in different market segments and are presented in a visual form in the table. The capitalization rate is calculated for hotels, one-room, two-room, three-room apartments. It is determined that the capitalization rate for hotels located in rural areas. Zhukovsky, Gagarin, Odesa, Oleksiyivka is about 23%. Thus, certain facilities are the most attractive for investment in the city of Kharkiv. As a result of the market research conducted by the authors, the interaction in the real estate rental and purchase and sale market within the development of Kharkiv’s municipal economy was analyzed. Development trends and directions of perspective investment in each segment of residential real estate and depending on the location are determined.